Optimization of Counseling by Bhabinkamtibmas to Prevent Drug Trafficking in Order to Achieve Public Security in the Demak Police Jurisdiction - Nouvel Izza Fardana (Tanggon Kosala, 2022)
The rise of drug trafficking cases that occurred in Demak Regency became a problem in this study. This study aims to describe Binluh by Bhabinkamtibmas as well as efforts to optimize Bhabinkamtibmas guidance and counseling activities in preventing drug trafficking in the jurisdiction of the Demak Police. This research method uses a qualitative approach with a descriptive analytical research type. The process of collecting data using interview techniques, and field observations. Data validity uses source triangulation, method triangulation, and theory triangulation. The concepts and theories used are SWOT analysis theory, 5M management theory, POAC theory and the concept of drug abuse, the optimization concept, the counseling guidance concept, the bhabinkamtibmas concept, and the drug concept. The factual condition based on the results of the research is that Binluh was not optimal by Bhabinkamtibmas in preventing drug trafficking at the Demak Police Station with the discovery of several faktors that influenced both internally and externally. In an effort to solve the problem being analyzed is to use the theory of Elements of Management 5M namely providing education to personnel, disseminating regulations on drug abuse, and establishing cooperation with other agencies. Furthermore, with the theory of Management Functions (POAC), namely maximizing planning in accordance with applicable regulations, dividing the area of extension guidance, and supervising and providingreward andpunishment to Bhabinkamtibmas members. Furthermore, by crossing the supporting faktors against the inhibiting faktors which are analyzed using the SWOT analysis theory. In reality, it is still necessary to optimize SDO Bhabinkamtibmas in the implementation of Binluh and to make careful planning before implementing activities so that the objectives of implementing Binluh can be achieved properly.